JOHN OF SALISBURY’S SYMBOLICAL BIOGRAPHY - Oana-Corina FILIP (Studia Universitatis Babeș-Bolyai. Philosophia, 2016)
John of Salisbury’s Symbolical Biography. The article John of Salisbury’s Symbolical Biography, is part of an ampler study upon the relationship between political philosophy and the philosophy of language in John of Salisbury’s Policraticus. The article focuses on the manner in which certain events in Salisbury’s life are reflected in the thematic of his work, particularly in the way he addresses the link between political philosophy and the philosophy of language.